Development of Emotional Intelligence (Emotional Intelligence) in Sports Learning Activities at School - Syifa Nurbait; Risa Herdiyana Bastian (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the results of the development of Emotional Intelligence (Emotional Intelligence) on school sports learning activities. The research method used is development research from Borg and Gall (2017) which has been varied, namely (1) conducting preliminary studies, (2) model development plans, (3) initial model development, (4) revision of validation results (5) small group field trials, (6) revision of test results (final product). The instrument used in this study used a questionnaire to measure Emotional Intelligence (emotional intelligence) made by Goleman (2016), which was then adapted by researchers according to research needs. Data was collected using a questionnaire obtained from expert evaluation, small group trial of 20 junior high school students in the city of Cirebon. The data are the results of an assessment of product quality, suggestions for product improvement, and the results of filling out questionnaires by students. The data analysis technique used is descriptive percentage to reveal student assessments using a product developed with the help of the Statistical Package for Social Science (SPSS). Based on the results of the explanation above, it is hoped that the development of Emotional Intelligence (emotional intelligence) will help students in their daily lives, to be able to increase positive interactions with their environment, and be able to use emotions and emotional knowledge in improving thinking. Physical education teachers in junior high schools are expected to use products for developing Emotional Intelligence (emotional intelligence) for learning activities in schools.